The master guide to controllers best practices - Stattler, Elaine; Grabel, Joyce Anne (Association of Accountants and Financial Professionals in Business, 2016)
Today's controllers are in leadership roles that put them in the unique position to see across all aspects of the operations they support. The Master Guide to Controllers' Best Practices, Second Edition has been revised and updated to provide controllers with the information they need to successfully monitor their organizations' internal control environments and offer direction and consultation on internal control issues. In addition, the authors include guidance to help controllers carryout their responsibilities to ensure that all financial accounts are reviewed for reasonableness and are reconciled to supporting transactions, as well as performing asset verification.